Effectiveness of Hypnotherapy and Classical Music Therapy on Anxiety of Third Trimester Pregnant Women at Winda Clinic in 2022 - Ismu Rohimah; Rahayu Khairiah; Arjuna Arjuna (STIKep PPNI Jawa Barat, 2023)
Aims: Pregnancy is a period of crisis for a woman. A process that matures and can cause stress. According to United Nations Children's Fund (UNICEF), 30% of 12,230,142 pregnant women experience anxiety. The way to overcome anxiety is nonpharmacological therapy, one of which is hypnotherapy and classical music therapy. Methods: Using a quasi experiment with a pretest and posttest group design, researchers observe participants before and after intervention without using a control group. With a sample size of 44 respondents, the sampling technique employed was purposive sampling. To assess variations in the effectiveness of hypnotherapy and classical music therapy on anxiety in third trimester pregnant women, data variables include nominal and ordinal scales, and data are analyzed with the Wilcoxon test with = 0.05 and the Mann-Whitney test. Results: There was a significant effect of anxiety level before and after hypnotherapy with a significance value of 0.000 (p0.05), and there was a significant effect of anxiety level before and after classical music therapy intervention with a significance value of 0.000 (p0.05). The Mann-Whitney Test demonstrates that there is no difference between the effectiveness of hypnotherapy and classical music because the value of Asymp. Sig. (2-tailed) >, where =0.05 is (0.832>0.05), thus Ho is accepted. Conclusion: Before and after the intervention, there is a significant difference between the effects of hypnotherapy and classical music therapy on reducing the anxiety level of expectant women. The combination of hypnotherapy and classical music therapy can help pregnant women unwind and provide early stimulation to the fetus, making it a viable intervention for pregnant women.